Exploring biocultural diversity: A systematic analysis and refined classification to inform decisions on conservation and sustainability - Otamendi-Urroz, Irene; Quintas‑Soriano, Cristina; Hanspach, Jan; Requena-Mullor, Juan Miguel; Lagies, Anna Sophie; Castro, Antonio J. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Biocultural diversity reflects the interplay among biological and cultural diversity within social-ecological systems, shaped by human societies’ unique interactions with nature. This concept encompasses diverse knowledge, beliefs, practices, and values linked to local biodiversity. Despite its growing relevance, research gaps persist, including the need for theoretical clarity and a broader empirical application. To examine biocultural diversity’s role in conservation and sustainability, we conducted a systematic mapping of scientific literature in English and Spanish from 1990 to 2021, using cluster analysis to identify research trends. Including Spanish literature broadened the analysis, offering unique perspectives often overlooked. Results reveal gaps on research, particularly regarding intangible biocultural components (e.g., traditional knowledge, values, or worldviews) and the need for research in underrepresented regions like Africa and Asia. To advance in this direction, we propose a novel classification for biocultural diversity to foster holistic understanding, encourage exploration of intangible components, and promote collaboration among stakeholders.
Keywords: Biocultural Approach; Biocultural Diversity Component; Cluster Analysis; Conservation Effort; Evidence Synthesis; Social-ecological System